Complex Geometry and Dynamics The Abel Symposium 2013 - Fornæss, John Erik; Irgens, Marius; Wold, Erlend Fornæss (Abel Symposia, 2015)
This book focuses on complex geometry and covers highly active topics centered around geometric problems in several complex variables and complex dynamics, written by some of the world's leading experts in their respective fields. This book features research and expository contributions from the 2013 Abel Symposium, held at the Norwegian University of Science and Technology Trondheim on July 2-5, 2013. The purpose of the symposium was to present the state of the art on the topics, and to discuss future research directions.